Teacher evaluation and Portfolio: analysis of teachers’ professional performance in Chile - Padilla Fuentes, Geraldo (2023)
This article explores the results of Teacher Evaluation in Chile during the last decade, especially those of the teacher portfolio and its subdimensions. The results show that, during the last years, unsatisfactory performance in the Teacher Evaluation has increased, mainly among male teachers and those who teach History. As regards the portfolio, it is the instrument with the lowest average results each year, especially its indicators of curricular emphasis and use of error for learning; the binary logistic regression indicates that the most favorable profile for an adequate performance in this instrument is linked to the female gender, secondary education, and the mathematics subsector. The conclusions discuss the role and usefulness of the portfolio in Teacher Evaluation and educational policy.